Kerja Sama Sister City Surabaya–Busan dalam Bidang Pendidikan Tahun 2015–2025 - Virda Rizky Anggraini; Farahdzilla Muthianisa Azzahra; Kin Ashiladafsa Blantiant; Ario Bimo Utomo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Sister City cooperation between Surabaya (Indonesia) and Busan (South Korea) has been ongoing since 1994 and covers various fields, one of which is education. This article aims to analyze the implementation of the educational cooperation program between Surabaya and Busan for the 2015–2025 period using Sister City analysis theory from a paradiplomacy perspective as the basis for the study. This research examines student exchange programs, teacher training, and scholarship support facilitated by the Busan Foundation for International Cooperation (BFIC) and the Surabaya City Education Office. The research method used is descriptive qualitative, with data obtained through document review of official government reports, websites, online news, and academic literature related to educational diplomacy. The results indicate that the student exchange program, the Global Youth Friendship Program, school visits, teacher training, and scholarships contribute to increasing educational capacity and strengthening cultural ties between the two cities. However, budget constraints, program sustainability, and reliance on annual policies indicate that this collaboration has not been fully institutionalized sustainably within the regional education policy structure. This article recommends increasing the integration of education programs within the Sister City Agreement and strengthening coordination between the two city governments for the long-term education agenda.